Repair Sequence and Recovery Time in Water Distribution Network Resiliency - Aquino, Janice Kaye (Archīum Ateneo, 2021)
Recent disasters highlighted that Water Distribution Systems (WDS) suffered greatly during seismic events. But people cannot afford to have extended water service interruption as it is essential for drinking; sanitation; and health. Thus; it is imperative that WDS provides adequate resistance to extreme events. And in the event of failure; it must recover back its functionality within short period. Resilience-based engineering ensures that infrastructures be robust to adequately resist seismic events and recover from failure fast. It also requires to have resources and redundant systems. This implies that WDS must satisfy resiliency requirements for it to function satisfactorily during and after seismic events. This study quantifies the resiliency of La Trinidad Water District (LTWD) through measuring the impacts of restoration sequences to recovery duration and knowing which sequence satisfies resiliency. LTWD; in Benguet; Philippines; is at risk to earthquake due to geologic and geographic setting; thus; it must be “resilient”. In this study; restoration strategies were conducted using constrained spanning trees to determine the most efficient network connectivity. Horn’s algorithm was applied to find the most efficient repair sequence. Results showed that restoration sequence is directly related to rapidity of resiliency. The shortest restoration resulted to a faster recovery to return back to its pre-event system functionality. For LTWD; restoration will take 8.62 days for full recovery.